2016
DOI: 10.1002/mnfr.201501007
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol targets mitochondria to halt cancer progression and metastasis

Abstract: Cancer continues to be the leading cause of death worldwide. Plants have a long history of use in the treatment of cancer. Honokiol (HNK) is an important bioactive compound found in the bark of Magnolia tree, and has been shown to inhibit cancer growth and metastasis in many cell types in vitro and in animal models. Resistance to chemotherapy and radiotherapy is the major obstacle for cure of cancer. Combination of HNK with many traditional chemotherapeutic drugs as well as radiation sensitizes cancer cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 108 publications
(137 reference statements)
2
43
0
Order By: Relevance
“…Main energy source from TCA cycle occurs in the mitochondria and dysfunctional mitochondrion cause diabetes, obesity and carcinogenesis [1921]. Knowing that mitochondria is essential to metabolism, we show herein that pyruvate transport blocking via deletion of the MPC1 gene has impact on the metabolism and biological behaviors in prostate cancer cells in vitro .…”
Section: Discussionmentioning
confidence: 76%
“…Main energy source from TCA cycle occurs in the mitochondria and dysfunctional mitochondrion cause diabetes, obesity and carcinogenesis [1921]. Knowing that mitochondria is essential to metabolism, we show herein that pyruvate transport blocking via deletion of the MPC1 gene has impact on the metabolism and biological behaviors in prostate cancer cells in vitro .…”
Section: Discussionmentioning
confidence: 76%
“…Honokiol has generated an extensive interest in cancer research due to its multi-functional effects such as inducing anti-tumor growth, anti-migration, anti-angiogenesis and anti-multiple drug resistance (Kumar et al, 2013; Pan et al, 2016). As a novel agent for cancer therapy, honokiol, targets multiple signaling pathways, including nuclear factor kappa B (NF-κB) (Ahn et al, 2006), signal transducers and activator of transcription 3 (STAT3), epidermal growth factor receptor (EGFR) (Leeman-Neill et al, 2010; Song et al, 2016) and mammalian target of rapamycin (m-TOR) (Lin et al, 2016), all of which have great relevance during cancer initiation and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmacological researches have suggested that HKL has anti-inflammatory, anti-bacterial, anti-oxidant, anti-tumor, anti-calmodulin, neuroprotective, and other effects (Fried and Arbiser, 2009; Shen et al, 2010; Lee et al, 2011; Woodbury et al, 2013; Pan et al, 2016). A recent study had reported that HKL could reverse cardiac hypertrophy by inhibiting cardiac fibroblasts proliferation and differentiation to myofibroblasts (Pillai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%